Lead and zinc content of cows' milk affected by varying traffic density. (10th March 2009) - Ozdemir, Saim; Dundar, Mustafa S.; Sengorur, Bulent; Senol, Ataman S.
This study was conducted to investigate the influence of vehicle emissions on zinc and lead content of cow's milk, grazing at 15 different locations near to roadsides in Sakarya, Turkey. The results obtained for zinc were between 1262 μg kg−1 and 6566 μg kg−1. An acceptable range of zinc content from various sides confirmed the absence of possible toxicological risks in this region. The lead levels ranged from 3.24 μg kg−1 to 80.69 μg kg−1. The levels of lead in milk samples collected from roadside pastures were higher than the regulatory limits and pose a health risk.